2021
DOI: 10.1080/08897077.2020.1784358
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Drug Misuse, other Substance Use, and Sexual Identity: The Significance of Educational Status and Psychological Distress in US Young Adults

Abstract: Background The aim was to examine the effects of sexual identity, educational status, and their interaction on the past-year prevalence of controlled prescription use and prescription drug misuse (PDM) in U.S. young adults, 18–25 years. Methods Data were from the 2015–2017 National Survey on Drug Use and Health (young adult N = 38,298). Past-year prescription opioid, stimulant and benzodiazepine use and PDM were outcomes, with PDM defined as use without a prescription or in ways not intended by the prescriber.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…LGBTQ+ people) often suffer even worse health disparities (Quinn & Dickson-Gomez, 2016;Quinn et al, 2017;Robertson et al, 2021), and thus intersectionality was an underlying theme of the Let's Connect intervention by design, and our results suggest this was an important feature. Mental health interventions specific to LGBTQ+ people are sorely needed, as LGBTQ+ people continue to have persistent risk factors for suicide (Transgender Law Center, 2012), substance use (Batchelder et al, 2021;Diaz et al, 2021;Klare et al, 2020), and poor health outcomes for HIV (Dorcé-Medard et al, 2021), cancer (Fuchs et al, 2021;Junejo & Sheikh, 2021), and hepatitis C (Deacon et al, 2013;Wang et al, 2021). This is especially true for those on the fringes of the LGBTQ+ community, such as those with less mainstream identities (such as being bisexual or having another less-well-recognized sexual orientation, or being trans or gender non-conforming), and those who were unhoused or unstably housed (Batchelder et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…LGBTQ+ people) often suffer even worse health disparities (Quinn & Dickson-Gomez, 2016;Quinn et al, 2017;Robertson et al, 2021), and thus intersectionality was an underlying theme of the Let's Connect intervention by design, and our results suggest this was an important feature. Mental health interventions specific to LGBTQ+ people are sorely needed, as LGBTQ+ people continue to have persistent risk factors for suicide (Transgender Law Center, 2012), substance use (Batchelder et al, 2021;Diaz et al, 2021;Klare et al, 2020), and poor health outcomes for HIV (Dorcé-Medard et al, 2021), cancer (Fuchs et al, 2021;Junejo & Sheikh, 2021), and hepatitis C (Deacon et al, 2013;Wang et al, 2021). This is especially true for those on the fringes of the LGBTQ+ community, such as those with less mainstream identities (such as being bisexual or having another less-well-recognized sexual orientation, or being trans or gender non-conforming), and those who were unhoused or unstably housed (Batchelder et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These measures (with possible values in parentheses) included: Current marital status (married vs. not married), along with number of times married (0, 1, 2,…; Kerridge et al, 2017 ); Family formation, including household size (1, 2, 3, …) and an indicator of currently living with at least one child under the age of 18 (yes/no; Weber, 2008 ); Current pregnancy status (yes/no; Charlton et al, 2020 ; Everett et al, 2017 , 2019a ); Current use of various types of contraceptives (e.g., condoms; yes/no, for each type; Charlton et al, 2013 , 2019 ); Current sexual activity without contraceptive use (yes/no, for those sexually active; Charlton et al, 2013 , 2019 ); Intention to have children in the future (yes/no; Shenkman & Abramovitch, 2021 ); Measures of current substance use, including past-month binge drinking; past-year cigarette smoking, including at the rate of a pack-per-day; marijuana use; and other illicit drug use (e.g., cocaine, crack, and crystal meth) (yes/no; Boyd et al, 2019 ; Drabble et al, 2021 ; Klare et al, 2021 ); Risky sexual behaviors, including number of current sex partners (0, 1, 2,…) and anal sex (ever/never; Parmenter et al, 2020 ; Ueda et al, 2020 ); and Measures of sexual health, including sexually transmitted diseases (ever had an STD/never had an STD, and past-year STD (yes/no); Gurnik et al, 2023 ; Everett et al, 2019a , 2019b ). …”
Section: Methodsmentioning
confidence: 99%
“…Measures of current substance use, including past-month binge drinking; past-year cigarette smoking, including at the rate of a pack-per-day; marijuana use; and other illicit drug use (e.g., cocaine, crack, and crystal meth) (yes/no; Boyd et al, 2019 ; Drabble et al, 2021 ; Klare et al, 2021 );…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the minority stress framework, a recent study has analyzed the odds of prescription drug misuse in sexual minorities in regression models with and without a psychological distress variable among young adults (18–25 years old) 17 . They found that past-year psychological distress accounted for a considerable share of the differences between individuals from sexual minorities and their heterosexual counterparts, suggesting that psychological distress might act as a confounder in the higher odds of prescription drug misuse among individuals belonging to sexual minorities.…”
mentioning
confidence: 99%